Classroom application of using visual stimuli in teaching and learning dynamics and pitch - Lee, Ka Ming (2014)
Listening is a common activity in music lessons. It is difficult for teachers to know whether students are learning by listening. In this study, visual stimuli include imagery, metaphor, and symbols, were introduced to students in the experimental group to learn dynamics and pitch. A control group received the same lessons without any visual stimuli. Both groups received the same tests, pre-test and post-test, after the two lessons. Tests were divided into two parts including choosing the correct dynamic changes and distinguishing higher or lower pitch for the melody.